2012
DOI: 10.5194/acp-12-9941-2012
|View full text |Cite
|
Sign up to set email alerts
|

Are simulated aerosol-induced effects on deep convective clouds strongly dependent on saturation adjustment?

Abstract: Abstract. Three configurations of a bulk microphysics scheme in conjunction with a detailed bin scheme are implemented in the Weather Research and Forecasting (WRF) model to specifically address the role of the saturation adjustment assumption (i.e., condensing/evaporating the surplus/deficit water vapor relative to saturation in one time step) on aerosol-induced invigoration of deep convective clouds. The bulk model configurations are designed to treat cloud droplet condensation/evaporation using either satur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
128
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(136 citation statements)
references
References 55 publications
8
128
0
Order By: Relevance
“…Morrison and Grabowski, 2011). However, while some argue (fairly) that this is at least in part due to the limitations of bulk schemes to fully represent aerosol-cloud interactions (such as saturation adjustment; Lebo et al, 2012), others argue that this is consistent with the concept of clouds as a buffered system hypothesised by Stevens and Feingold (2009). Month-long simulations approaching the climatological scale using bin microphysics performed by Fan et al (2013) also showed aerosol impacts on precipitation on the order of a few percent.…”
Section: Introductionmentioning
confidence: 55%
See 4 more Smart Citations
“…Morrison and Grabowski, 2011). However, while some argue (fairly) that this is at least in part due to the limitations of bulk schemes to fully represent aerosol-cloud interactions (such as saturation adjustment; Lebo et al, 2012), others argue that this is consistent with the concept of clouds as a buffered system hypothesised by Stevens and Feingold (2009). Month-long simulations approaching the climatological scale using bin microphysics performed by Fan et al (2013) also showed aerosol impacts on precipitation on the order of a few percent.…”
Section: Introductionmentioning
confidence: 55%
“…Lynn and Khain (2007) found that, while all schemes overestimated maximum rain rates in a simulated MCS, all bulk schemes tested overpredicted average and maximum rain rates by a factor of 2 to 3, while bin schemes overestimated maximum rain rates by about 20 %. In idealised supercell simulations, Khain and Lynn (2009) found that the Thompson et al (2004) double-moment bulk scheme produced 2 times more accumulated surface rain than a bin scheme, while Lebo et al (2012) found that the bulk scheme also produced twice as much surface rain as the same bin scheme used by Khain and Lynn (2009) in simulations of the same supercell. Investigations of the shape of the cloud droplet size distribution in large-eddy simulations of non-precipitating shallow cumulus clouds with a bin (Igel and van den Heever, 2017a) and bulk (Igel and van den Heever, 2017b) scheme showed the importance of the cloud droplet size distribution shape parameter.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations